A Pseudo‐Regular Alternating Conjugated Copolymer Using an Asymmetric Monomer: A High‐Mobility Organic Transistor in Nonchlorinated Solvents. (5th May 2015) - Choi, Hyun Ho; Baek, Jang Yeol; Song, Eunjoo; Kang, Boseok; Cho, Kilwon; Kwon, Soon‐Ki; Kim, Yun‐Hi
Abstract : Pseudo‐regular alternating PDPP–TVS copolymers using an asymmetric monomer (thiophene–vinylene–selenophene (TVS)) are synthesized. Unlike regular alternating copolymers, these polymers are highly soluble in nonchlorinated solvents such as tetrahydrofuran, toluene, xylene, and tetralin. The organic field‐effect transistor devices fabricated using these polymers dissolved in nonchlorinated solvents exhibit a high hole mobility up to 8.2 cm 2 V −1 s −1 .